1999
DOI: 10.1086/315009
|View full text |Cite
|
Sign up to set email alerts
|

Immunogenicity and Impact on Nasopharyngeal Carriage of a Nonavalent Pneumococcal Conjugate Vaccine

Abstract: The safety, immunogenicity, and impact on carriage of a nonvalent pneumococcal vaccine given at ages 6, 10, and 14 weeks were examined in a double-blind, randomized, placebo-controlled trial in 500 infants in Soweto, South Africa. No serious local or systemic side effects were recorded. Significant antibody responses to all pneumococcal serotypes were observed 4 weeks after the third dose. Haemophilus influenzae type b polyribosylribitol phosphate (geometric mean titer, 11.62 microg/mL) and diphtheria (1.39 IU… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

17
266
3
8

Year Published

2000
2000
2009
2009

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 482 publications
(297 citation statements)
references
References 26 publications
(27 reference statements)
17
266
3
8
Order By: Relevance
“…Previous studies have documented reduced carriage of vaccine-included strains after immunization. 16,22,23 Our data confirm that PCV7 immunization substantially reduced carriage with PCV7 serotypes, but immunization was not associated with lower rates of S pneumoniae carriage overall. This is additional indirect evidence for serotype replacement among organisms colonizing the nasopharynx after immunization.…”
Section: Discussionsupporting
confidence: 59%
See 1 more Smart Citation
“…Previous studies have documented reduced carriage of vaccine-included strains after immunization. 16,22,23 Our data confirm that PCV7 immunization substantially reduced carriage with PCV7 serotypes, but immunization was not associated with lower rates of S pneumoniae carriage overall. This is additional indirect evidence for serotype replacement among organisms colonizing the nasopharynx after immunization.…”
Section: Discussionsupporting
confidence: 59%
“…20,21 However, children remain at risk from serotypes not included in PCV7. Colonization with pneumococcal vaccine serotypes 16,22,23 has been shown to decrease shortly after immunization, but longer-term changes in colonization patterns in communities remain unclear. The possibility exists that serotypes with which children have traditionally been colonized may be replaced by nonvaccine serotypes as predominant colonizers in a community, possibly leading to increased risk of infection by these organisms.…”
mentioning
confidence: 99%
“…In the largest BCG trial conducted in the same region earlier, BCG did not afford any protection. It is known that genetic variation of the strains is a method of vaccine escape and has been demonstrated in several bacterial species (Van Loo et al, 2002, Mbelle et al, 1999. Further investigation in this line would be helpful to ascertain the role of these highly prevalent strains on the host immunity.…”
Section: Discussionmentioning
confidence: 99%
“…In the controlled trial done in Soweto, South Africa by Mbelle and associates, results showed that vaccination with a 9-valent pneumococcal vaccine significantly reduced nasopharyngeal carriage of serotypes 19F and 6B. 104 Serotypes 6A and 6B differ only in the linkage of a single sugar in the carbohydrate molecule, and it is of some concern that the vaccine did not reduce carriage of serotype 6A. 114 Fifteen percent of the residual nasopharyngeal carriage of antibiotic-resistant strains in the study was due to the continued carriage of serotype 6A.…”
Section: Future Challenges and Considerationsmentioning
confidence: 99%
“…The impact of a conjugate vaccine on pneumococcal carriage was studied by Mbelle and colleagues. 104 The study evaluated the safety, immunogenicity, and impact on carriage of a pneumococcal 9-valent (serotypes 1, 4, 5, 6B, 9V, 14, 18C, 19F, and 23F) conjugate vaccine (PNCRM9). The 9-valent vaccine was administered at ages 6, 10, and 14 weeks in a double-blind, randomized, placebo-controlled trial in 500 infants in Soweto, South Africa.…”
Section: Safety and Immunogenicity Of Pneumococcal Conjugate Vaccinesmentioning
confidence: 99%